Second course of stereotactic radiosurgery for locally recurrent brain metastases: Safety and efficacy. - Juliette Moreau; Toufic Khalil; Guillaume Dupic; Emmanuel Chautard; Jean-Jacques Lemaire; Florian Magnier; Véronique Dedieu; Michel Lapeyre; Pierre Verrelle; Julian Biau (PLoS ONE, 2018)
In the present study, we have evaluated the efficacy and toxicity of repeated brain metastases (BM) stereotactic radiosurgery (SRS2) following local failure of a prior radiosurgical procedure (SRS1). Between December 1996 and August 2015, 30 patients with 36 BM underwent SRS2 with a median dose of 18Gy. All BM were located outside critical structures. Following SRS2, local control at 6 months and one year were respectively 82.9% (IC 95%: 67.6-91.9) and 67.8% (IC 95%: 51-81). On multivariate analysis, planning target volume (PTV) < 3cc (HR: 0.19 (0.1-0.52)) and whole brain radiotherapy (WBRT) prior to SRS2 (HR: 0.25 (0.1-0.64)) were significantly associated with a better local control. One- and two-year overall survival rates after SRS2 were respectively 65.5% (IC 95%: 47.3-80%) and 27.6% (IC 95%: 14.7-45.7). Median overall survival following SRS2 was 14.2 months (range 1-106). Nineteen (63%) patients died from progressive systemic disease. Three (10%) patients died from out-field progressive brain disease and 8 (27%) in-field. Concerning toxicities, edema, radionecrosis, and hemorrhages were identified in 5 (12.8%), 4 (10.2%), and 5 (12.8%) patients respectively. No toxicity resulted in a neurological deficit. On univariate analysis, toxicities were significantly associated with PTV > 7cc (p = 0.02) and all patients had a WBRT before SRS2. A second course of SRS for locally recurrent brain metastases showed encouraging rates of local control. This treatment led to acceptable toxicities, especially for brain metastases smaller than 7cc, in our selected cohort of patients with BM located outside critical structures. Further studies are needed.